Adsorption and release of soil P in andisols under organic and conventional vegetable farming system - Aridinasty Maritasari; Benito Heru Purwanto; Sri Nuryani Hidayah Utami (Jurnal Ilmu Pertanian, 2022)
Phosphorous (P) is strongly adsorbed by soil components, such as soil organic matter and soil amorphous minerals in Andisols, which have been identified as an influential factor in adsorption and release of soil P. The aim of this study was to characterize the pattern of soil P adsorption and release in both organic and conventional vegetable farming systems in Merbabu Mountain area, Indonesia. Soil samples were collected from soil layers (0 cm to 20 cm and 20 cm to 40 cm) in organic and conventional farming systems. The result showed that the highest adsorption rate was found in organic farming systems at a depth of 20 cm to 40 cm. The lowest adsorption rate was found in conventional farming systems with low input of organic matter at a depth of 20 cm to 40 cm. A higher rate of P release was also found in organic farming systems with a low input of organic matter. It can be concluded that vegetable soils in organic farming systems are not only highly capable of adsorbing P but also capable of releasing P rapidly.